Polyadenylic acid in the genomic RNA of mengovirus. - Marshall, M V (1976)
The polyadenylic acid contained in 35S mengovirus RNA produced in infected BHK-21 cells contained approximately 94% AMP and was estimated to contain an average of 50 to 55 nucleotides. The polyadenylic acid is placed at the 3'-end of the genomic RNA based on the presence of significant levels of [3H]adenosine in complete alkali or RNase T2 digests of polyadenylic acid from [3H]adenosine-labeled 35S viral RNA.